2019
DOI: 10.2147/tcrm.s177603
|View full text |Cite
|
Sign up to set email alerts
|

<p>Barriers to achieving asthma control in adults: evidence for the role of tiotropium in current management strategies</p>

Abstract: Despite the availability of a range of treatment options and management guidelines, a high proportion of adults with asthma remain uncontrolled. The challenge of managing uncontrolled asthma includes providing efficacious treatment while limiting side effects, recognizing situations when a change in asthma therapy is required, and considering patient preferences and satisfaction. In line with the Global Initiative for Asthma report, asthma management is based on a backbone of inhaled corticosteroid (ICS) thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…Among LAMAs, tiotropium has been used most widely and for a long time. 25 Tiotropium RespimatÒ is approved in asthmatic patients aged 6 years and older in Korea, the United States, and the European Union. 25,26 Several studies have elucidated the efficacy of tiotropium in asthma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among LAMAs, tiotropium has been used most widely and for a long time. 25 Tiotropium RespimatÒ is approved in asthmatic patients aged 6 years and older in Korea, the United States, and the European Union. 25,26 Several studies have elucidated the efficacy of tiotropium in asthma.…”
Section: Discussionmentioning
confidence: 99%
“…25 Tiotropium RespimatÒ is approved in asthmatic patients aged 6 years and older in Korea, the United States, and the European Union. 25,26 Several studies have elucidated the efficacy of tiotropium in asthma. A double-blind, three-way, crossover trial, called the Tiotropium Bromide as an Alternative to Increased Inhaled Glucocorticoid in Patients Inadequately Controlled on a Lower Dose of Inhaled Corticosteroid (TALC) study, revealed that adding tiotropium is superior to increasing ICS dose in patients whose asthma symptoms are not controlled by inhaled beclomethasone alone at a dose of 160 mg/day, and non-inferior to adding salmeterol with respect to morning and evening peak expiratory flow (PEF) and asthma symptom score.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we still do not understand why these subsets of people do not respond to corticosteroids (Henderson et al 2020 ). Many theories have been suggested ranging from genetics to patient non-adherence (Jenkins 2019 ), but could the lung microbiome have a role to play (Barcik et al 2020 )? Barcik and colleagues in 2020 discussed the connection between the gut and lung and how the microbiota plays a bidirectional interaction between the two sites.…”
Section: Introductionmentioning
confidence: 99%
“…2,5 And yet, despite the availability of a wide range of treatment options, a large body of research has indicated that effective implementation of clinical guidelines is lacking, corresponding with steady, high rates of uncontrolled asthma. 6,7 Within the literature, asthma control refers to the severity of symptoms and risk of poor outcomes experienced by a patient, despite use of a prescribed therapy. 5 Asthma is classified as uncontrolled when it involves poor symptom control (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…2,5 And yet, despite the availability of a wide range of treatment options, a large body of research has indicated that effective implementation of clinical guidelines is lacking, corresponding with steady, high rates of uncontrolled asthma. 6,7…”
Section: Introductionmentioning
confidence: 99%